Financing constraints and fixed-term employment: Evidence from the 2008-9 financial crisis - Fernandes, Ana P. (2017)
This paper investigates the effect of the 2008–9 financial crisis on firms’ employment composition decision when it is possible to choose between permanent and fixed-term workers. We use linked employer-employee data for the universe of private sector firms in Portugal, and exploit precrisis variation in financial vulnerability across industries for identification. We find that firms in more financially constrained industries hire a larger proportion of fixed-term workers with respect to permanent workers after the 2008-9 crisis, relative to less financially vulnerable firms. At the worker-level, workers hired by firms in industries that require significant external financing are more likely to be hired with a fixed-term contract after the crisis than comparable workers hired by other firms. Our results suggest that the crisis induced financially constrained firms to use the more flexible fixed-term contracts more intensively.